Does the Oil Price Adjust Optimally to Oil Field Discoveries? - Lisa Leinert (ETH Zurich, CER-ETH - Center of Economic Research, 2012)
The Hotelling rule argues that the price for a non-renewable resource adjusts to the shadow value of the resource, reflecting its remaining availability. This study provides an empirical test of this hypothesis. It investigates whether the price of crude oil does adjust to unexpected news about oil field discoveries. The observed price reaction is compared with a prediction of the price decline as derived from the Hotelling model. This study finds evidence for an adjustment of the price to news about greater resource availability: the price of crude oil declines on average by 0.88% on discovery days. The degree of adjustment to the new level of scarcity is not found to differ significantly from the social optimum. Thus, there is evidence for the existence of a shadow cost component - a necessary pre-requisite for the Hotelling rule to hold.
Keywords: Q31; Q41; Q14; 330; Non-renewable resources; Oil Price; Exhaustible Resources; Ölpreis; Exploration; Erdölvorkommen; Hotelling-Regel; Welt